End of the Rainbow - Nugent, Robert (Australia, 2007)
Verzio FF A multinational mining company negotiates with the Guinean government before beginning to mine gold in the West African country, paying the original inhabitants compensation. As soon as the mine goes into operation the multinational provides work to poor local villagers. However, inevitable misunderstandings and conflict gradually arise between the community and the white gold–miners, with the investors calling on the army to quell the trouble. This tribal society, which has for years been dependent on small finds of gold, has barely any understanding of the rules of a globalized economy, let alone the opportunity it creates for carpetbagging. The villagers keep searching illicitly for the precious metal, ending up in jail if they are caught. When the mining company leaves with its gold bars what remains is a stripped landscape and greater poverty than before. The film is not concerned with political or ideological rhetoric; it is more a meditation on how traditional societies are finding it ever harder to resist developed modern civilization.